Myasthenic crisis as the first presentation of myasthenia gravis: A case report - Alvin Oliver Payus; Justin Leow Wen Hsiang; Leong Jia Qian; Azliza Ibrahim; Azman Ali Raymond (International Scientific Literature, Inc, 2021)
Myasthenic crisis is a condition characterized by the sudden onset of myasthenic weakness involving the respiratory muscles and requires ventilatory support to prevent death. This is a case report of respiratory failure in a 43-year-old man as the first presentation of myasthenia gravis.